1999
DOI: 10.1021/ic9809815
|View full text |Cite
|
Sign up to set email alerts
|

Substitution and Reduction of Platinum(IV) Complexes by a Nucleotide, Guanosine 5‘-Monophosphate

Abstract: A series of Pt(IV) anticancer complexes with different reduction potentials has been investigated for their reactivity toward 5'-guanosine monophosphate (5'-GMP). The Pt(IV) complexes studied were Pt(IV)(trans-d,l)(1,2-(NH(2))(2)C(6)H(10))Cl(4) (tetraplatin, Pt(IV)(dach)Cl(4); dach = diaminocyclohexane), cis,trans,cis-[Pt(IV)((CH(3))(2)CHNH(2))(2)(OH)(2)Cl(2)] (iproplatin, Pt(IV)(ipa)(2)(OH)(2)Cl(2); ipa = isopropylamine), cis,trans,cis-[Pt(IV)(en)(OH)(2)Cl(2)] (Pt(IV)(en)(OH)(2)Cl(2); en = ethylenediamine), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…Reduction could be catalyzed in the presence of Pt(II), however, Pt(II) does not need to be an analog to Pt(IV) to accelerate the substitution [17]. Using different methods of analysis confirmed that two electrons needed for the reduction come from the sugar portion of 5 0 -GMP [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Reduction could be catalyzed in the presence of Pt(II), however, Pt(II) does not need to be an analog to Pt(IV) to accelerate the substitution [17]. Using different methods of analysis confirmed that two electrons needed for the reduction come from the sugar portion of 5 0 -GMP [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Published results for the substitution of different Pt(IV) complexes show that their reactivity depends on their reduction potential [13,16]. For diammine complexes of platinum, the structure variation of diammine ligand has less effect on the rate of reduction, but the nature of axial ligands has higher influence on reduction potential [13,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand substitution reactions using [PtCl 4 (dach)] (dach ¼ cisand trans-1,2-diaminocyclohexane) failed or resulted in platinum(II) complexes [28,29]. In some cases intermediate platinum(IV) complexes could be detected [7,30]. A spontaneous reduction of a 9-methylguanine platinum(IV) complex is reported when dissolved in water [21].…”
Section: Introductionmentioning
confidence: 99%
“…A spontaneous reduction of a 9-methylguanine platinum(IV) complex is reported when dissolved in water [21]. Furthermore, it was found that Pt(II) may accelerate ligand substitution reactions of Pt(IV) complexes [4,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%